2018
DOI: 10.1371/journal.pone.0206879
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiological effects and proton RBE determined by wildtype zebrafish embryos

Abstract: The increasing use of proton radiotherapy during the last decade and the rising number of long-term survivors has given rise to a vital discussion on potential effects on normal tissue. So far, deviations from clinically applied generic RBE (relative biological effectiveness) of 1.1 were only obtained by in vitro studies, whereas indications from in vivo trials and clinical studies are rare. In the present work, wildtype zebrafish embryos (Danio rerio) were used to characterize the effects of plateau and mid-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…We therefore conclude that the effects of EP on survival are more similar to X-ray photons, at least as long as the MEFs have an intact DNA repair machinery (NHEJ, HRR). These observations corroborate findings obtained by others describing higher RBE values in a zebrafish model at mid SOBP compared to EP proton irradiation [71].…”
Section: Discussionsupporting
confidence: 92%
“…We therefore conclude that the effects of EP on survival are more similar to X-ray photons, at least as long as the MEFs have an intact DNA repair machinery (NHEJ, HRR). These observations corroborate findings obtained by others describing higher RBE values in a zebrafish model at mid SOBP compared to EP proton irradiation [71].…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis of existing in vivo data from 2002 found no significant variation in the RBE and ratified the use of a constant RBE of 1.1 (Paganetti et al 2002). However, more recent experiment work on animal models, irradiated with multiple LETd values, have indeed indicated that there is a correlation between increased LET and RBE (Sørensen et al 2017, Saager et al 2018, Szabó et al 2018.…”
Section: The Effect Of Variable Rbementioning
confidence: 96%
“…In order to exclude potential LET (linear energy transfer) effects of low energy protons at the end of the proton path [7] irradiations were performed at the entrance plateau of the proton beam depth dose profile. Radiobiological effects of Flash versus conventional proton treatment were assessed by rating their influence on embryonic survival and the formation of morphological abnormalities [8].…”
Section: Introductionmentioning
confidence: 99%